Nutrition, Sleep, and Exercise as Healthy Behaviors in Schizotypy: A Scoping Review - Keri Ka-Yee Wong; Adrian Raine (Behavioral Sciences, 2022)
This scoping review identifies the role of nutrition, sleep, and exercise as healthy behaviors in non-clinical individuals with schizotypy throughout the lifespan. Methods: We systematically reviewed the existing literature on these topics through databases including: PsycINFO, Scopus, APA PsycNet, ScienceDirect, Wiley Online Library, and SpringerLink. Results: Of the 59 studies found, a total of 29 studies met the inclusion criteria on the review topic. Included studies reflect varying study designs (cross-sectional, multiple time-point, intervention, randomized-placebo controlled trials), assessment of schizotypy and associated healthy behaviors, focus on various samples and lifespan (e.g., undergraduates, adolescents, at-risk individuals), and stem from different countries. Conclusion: While a moderate number of studies address the role of nutrition, sleep, and physical exercise in relation to schizotypy, studies intersecting these topics are limited. Of the limited studies that do exist, the majority are correlational with the beginnings of causal support from intervention studies. As such, more research is needed on the topics of nutrition, sleep, and exercise in relation to schizotypy. Specifically, future research should focus on providing a more holistic understanding of schizotypal traits and its subtypes, and which specific or combination of behaviors may reduce levels of schizotypy.